SEMI AUTOMATIC SPRAYER: SPRAYER INNOVATION- CARRY FREE AND ENERGY SAVING - Priyatmoko, Aris (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Sprayer is a pesticide applicator tool which is used to control pests and plant diseases. The main problem of the hand sprayer is that it has to be picked up, so that the farmers should deal with the weight. A sprayer, that takes gasoline motor or batteries as power source, will manage the operating and maintenance costs high. Based on these problems, the idea to innovate the hand sprayer arises, by modifying it to be semi-automatic sprayer, which is carry-free and energy saving. The principle work is the use of force resulted by wheel rotational motion, converted into translational motion to drive the pump rod as the air compressor. The air produced by the pump, is routed through the hose, and is then mixed with the sprayed fluid. Its dimension has a width of 44 cm, a length of 67 cm, and a heigth of 55 cm, so it can be used in chili plants area, and vegetables which are generally 60 cm distance in block. The use of semi-automatic sprayer will address the needs and problems faced by farmers, which is more cost-effective treatments, more efficient in crop spraying, and lighter in use, thereby it increases the farmersâ efficiency and productivity. Based on the experiments and analyses that have been done before, semi-automatic sprayer is able to increase farmers productivity up to 112%.Keywords: hand sprayer, agriculture, semi automatic, sprayer.